Diamond Jenness (1886-1969) - Helmer, James (ARCTIC, 1983)
. Jenness quickly found his curiosity about anthropology blossoming into a vocation. In 1911 he was appointed Oxford Scholar to Papua, New Guinea, where he spent twelve months studying the Northern Entrecasteaux. Upon his return to New Zealand, he was asked to join the Canadian Arctic Expedition, an ambitious government-funded scientific enterprise under the direction of the well-known arctic explorers Vilhjalmur Stefansson and R.M. Anderson. In June, 1913, Jenness found himself aboard the refitted whaling vessel Karluk steaming northward to the Bering Strait and beyond to the Beaufort Sea. . In the autumn of 1913, the small vessel became locked in the sea ice off the northern coast of Alaska. Unable to free itself, the ship drifted helplessly westward towards the Siberian Sea, where it was finally crushed in the ice off Wrangel Island. Eight men perished in their bid to reach the mainland. By a stroke of fortune, Jenness was not aboard the Karluk when she drifted off; he, Stefansson, and several others had left the ship earlier on a routine hunting trip. Abandoning the hopeless task of searching for the Karluk, which was lost to sight when they returned, the hunting party headed for Barrow, Alaska to rendezvous with the remaining two vessels of the expedition, the Alaska and the Mary Sachs. Jenness spent his first winter at Harrison Bay, Alaska, where he learned to speak Inuktitut, gathered information about Western Eskimo customs and folklore, and experienced at first-hand the precarious existence of the northern hunter. In the spring of 1914, he set out along the coast to the expedition's base camp at Bernard Harbour in the Coronation Gulf region. Here he engaged in one of the most important goals of the Canadian Arctic Expedition-the study of the Copper Eskimos of Victoria Island, a people first brought to the attention of the "civilized world" by Stefansson only four years earlier. When Jenness arrived in the Coronation Gulf region, only a handful of Europeans had visited the land of the Copper Eskimo. ...